Food and Nutrition Security in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The radio features in this pack address the topical issues of tackling food and nutrition security, with an emphasis on the use of information and communication tools, within the Caribbean states.